Effectiveness of the total absorption on noise reduction in industrial plants - Ilgurel, Nuri (INST NOISE CONTROL ENGINEERING, 2013)
This study investigates the noise reduction levels on acoustical models of an existing production plant due to the total absorption. Noise measurements have been carried out in this plant in order to determine the actual noise levels emitted by different types of machinery and the workers' noise exposure. The production plant has been acoustically simulated in order to evaluate the noise attenuations for various absorption configurations comprising low (actual situation), medium and high absorptive states of wall, ceiling and wall-ceiling surfaces together. The effectiveness of each absorption configuration has been evaluated regarding the amount of the assigned absorption and achieved noise reduction for the workers' positions and also for the entire production area. It can be clearly stated that the choice of the absorptive material and the place of the absorptive surface inside the production plant are both significant factors to obtain the desired reduction in noise levels and an acceptable distribution of the noise levels in the production plant. As the result of the study an equation is proposed, which gives the possibility to determine the effectiveness of the used absorption by considering the noise reduction gain compared to the used amount of absorption. (C) 2012 Institute of Noise Control Engineering.
Keywords: Acoustics; Engineering